Automatic formed cotton buds delivery agent of antiparasitic drugs from Annona muricata leaves as a preventive and curative therapy towards Otodectes cynotis infection in pets: An in vivo proof of concept study - Jamaluddin, Abdul Wahid; Ciputra, Lyvia Angeline; Mappiara, Muhammad Afiq S.; Minarfa, Tiara S; Rizal, Yuki Nurindar (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2024)
The practice of keeping pet animals have gained popularity in society, with the owning number of pets that reach 67%, particularly 37% for cats and 16% for dogs. Since animals have been considered family members nowadays, keeping them means that the owner is willing to contribute to maintaining their health and hygiene, which is crucial to prevent the spread of diseases that can affect both the pet and their owner. One common issue in animal health is the infection caused by the ear mite called Otodectes cynotis, which can lead to external ear canal inflammation. Current treatment for Otodectes cynotis infection is utilizing the topical application of synthetic drugs that contain antiparasitic synthetical drugs inside such as ivermectin and doramectin, due to the potential side effects and the threat caused by the tight therapy dose index in antiparasitic drugs, the alternative treatments including modified cotton buds and the use of herbal remedies have been developed to upgrade, to solve and to invent the novelty of science. This research aims to prove the hypothesis of the effectiveness of soursop leaf extract in eradicating Otodectes cynotis in animals, prescribing the required concentration to generate effective results yet to investigate the potential of modified cotton buds as a product of equipment. The outcomes of this study are expected to facilitate the development of knowledge in parasitic drugs and herbal medicine substitutes yet to innovate the more practical way to perform drug therapy for external otitis in pet animals caused by Otodectes cynotis